Species Composition and Community Structure of Small Pelagic Fish Landed at Pondokdadap Coastal Fishing Port, East Jawa - Indonesia - Satria Gemilang; Husain Latuconsina; Hamdani Dwi Prasetyo; Anthon Andrimida (BIOSAINSTEK, 2026)
Management of small pelagic fish resources for sustainable use requires scientific information related to exploited fish resources, related to species composition, and community structure, including conservation status. This study aims to analyze the species composition, frequency of occurrence, community structure, and conservation status of small pelagic fish caught by fishermen. This study was conducted in April - May 2025 at the Fish Auction Place and Fishermen's Fish Market at Pondokdadap Beach Fishing Port, Sendangbiru, Malang Regency, East Java. The method used was direct observation with species identification and analysis of species composition, frequency of occurrence, and community structure. The results showed that the small pelagic fish group consisted of six species with a total of 5,332 individuals, dominated by Rastrelliger brachysoma and Decapterus macarellus, with the highest composition and frequency of occurrence. The community structure of small pelagic fish includes Diversity and Dominance indices which are in the low category with values of 1.20 and 0.38, respectively, and the Evenness index which is in the unstable category with a value of 0.67. The species composition and community structure of small pelagic fish fluctuate significantly daily and seasonally, linked to the dynamics of environmental parameters that influence fish biological activity, as well as the complexity of the food chain and fishing pressure. The varying catch sizes of individual small pelagic fish species indicate low gear selectivity. Therefore, regulations governing biologically appropriate fishing practices, supported by further research on reproductive biology and population dynamics, are essential to support sustainable utilization.